Hubungan Motivasi Belajar Dengan Berpikir Komputasi Mahasiswa PGSD UNS Surakarta - M. Argiadi Ramadhan; Rukayah Rukayah; Roy Ardiansyah (Universitas Sebelas Maret, 2026)
The rapid development of technology requires every individual to follow these developments in the world of education, one of which is the skill that must be mastered, namely computational thinking skills. These skills play a role in solving mathematical problems that use abstract, logical ways of thinking, and following algorithmic steps. The use of a student-centered learning approach in teaching computational thinking can increase a person's motivation to learn. This study aims to determine the relationship between learning motivation and computational thinking skills of PGSD UNS Surakarta students. This research is a type of quantitative research with a correlation approach. The research data was taken from second-semester students of PGSD UNS Surakarta for the 2022/2023 Academic Year. Data were collected through Likert-based psychological tests and scales. Data analysis includes prerequisite tests (normality and linearity tests) and hypothesis tests with simple correlations. The results showed that there was no positive and significant relationship between learning motivation and computational thinking skills, with a significance value of 0.421 > 0.005 and Pearson Correlation 0.098 which showed a very low relationship category. It is recommended to increase learning motivation to become independent learners, as well as develop computational thinking skills to better manage the mind and learning process.